Overview on performance of water scrubber systems in reducing odour at raw natural rubber processing factories in Malaysia / Fatin Hamimi Alias - Alias, Fatin Hamimi; Mohammad, Mohd Ikram; Idris, Nur Fadhilah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
The upcoming Odour Regulation enforcement by the Department of Environment (DOE) sets an odour discharge limit at point of emission of not more than 25,000 ou/m3 at all times for all raw rubber processing factories. The major source of malodour is from the release of volatile organic compounds (VOCs) via exhaust gas during the drying activity and is presently controlled by using water scrubber treatment systems. In the present study, the operating conditions and performances of a scrubber from a local Standard Malaysian Rubber (SMR) factory was evaluated to find factors affecting high odour discharge levels. Poor performance of scrubbers was due to low scrubbing efficiency and this was attributed by the acidic pH levels of scrubbing liquid and high air flow rates. High odour concentration levels of the drier’s exhaust gas were due to high volatile content in the raw rubber. Some design recommendations made include suggestions in installing gauges to monitor and control contributing factors hampering scrubber performance.